Terminal / 6. - Gordon, Roderick (Gordon, Roderick. Tunnels series., 2013)
"Styx and their cohorts of deadly Armagi have swept across England, leaving death and devastation in their wake. Only a miracle can save the day and, in the inner world at the centre of the earth, Will and Elliott might just have stumbled upon one as they uncover ancient secrets that are fundamental to all human and Styx life"--Provided by publisher.